Percepções de futuras professoras que ensinarão matemática sobre o papel do estágio na formação inicial - Baima, Jéssica de Godoi (Universidade Federal de São Carlos, 2024)
This work refers to a Master's thesis, linked to the Postgraduate Program in Education (PPGE) at the Federal University of São Carlos (UFSCar), line of research in Science and Mathematics Education, Mathematics Education axis. The general objective lies in understanding the possibilities and contributions of the mandatory internship, linked to the Degree Course in Pedagogy at UFSCar, to the Mathematics curricular component based on the perceptions of future teachers. To this end, an intervention-type investigation was carried out with a group of students so that they could reflect on the role of the internship in teaching Mathematics based on their subjects, with proposals linked to problem solving in an approach under Gérard Vergnaud's Conceptual Field Theory (1990). In a collaborative way with the participants, there was a focused and oriented look at the study and appropriation of the theoretical-methodological framework that guided the organization of interventions in schools. Furthermore, a focus group was created as a central data production instrument, which aimed to identify perceptions, feelings, strategies and ideas about how the internship can be a field of research. In addition to the group sessions, individual semi-structured interviews were carried out, which provided the understanding that the internship underwent some modifications after the COVID-19 pandemic, but still has an important role in the training of future teachers, with potential for research in Mathematics. It was concluded that it is possible to use the internship environment as a field of contribution to the place of Mathematics Education in the Pedagogy course, as long as there is a reflection on the distribution of the internship workload and its configuration and/or orientation. It is also necessary to strengthen the partnership between the University and school institutions.
Perceptions of future teachers who will teach mathematics on the role of the internship in initial training
Keywords: Estágio; Formação de professores; Educação matemática; Teoria dos campos conceituais; Internship; Teacher training; Mathematics education; Conceptual field theory; CIENCIAS HUMANAS::EDUCACAO